Longitudinal changes in lung function in very prematurely born young people receiving high‐frequency oscillation or conventional ventilation from birth. Issue 6 (18th April 2022) - Bisquera, Alessandra; Harris, Christopher; Lunt, Alan; Zivanovic, Sanja; Marlow, Neil; Calvert, Sandy; Greenough, Anne; Peacock, Janet L.
Abstract: Objective: To examine changes in lung function over time in extremely prematurely born adolescents. Working Hypothesis: Changes in lung function during adolescence would vary by ventilation mode immediately after birth. Study Design: Longitudinal follow‐up study. Patient Subject Selection: Participants from the United Kingdom Oscillation Study who were randomized at birth to high‐frequency oscillation (HFO) or conventional ventilation (CV) were assessed at 11–14 years ( n = 319) and at 16–19 years ( n = 159). Methodology: Forced expiratory flow (FEF), forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and lung volumes including functional residual capacity (FRC) were reported as z‐scores. The diffusion capacity of the lungs for carbon monoxide (DLCO) was measured. Lung function trajectories were compared by mode of ventilation using mixed models. Changes in z‐scores were scaled to 5‐year average follow‐up. Results: There were significant changes in the mean FEF75, FEF50, FEF25, FEV1, FVC, and DLCO z‐scores within the CV and HFO cohorts, but no significant differences in the changes between the two groups. The mean FRC z ‐score increased in both groups, with an average change of greater than one z ‐score. The mean FEV1/FVC z‐score increased significantly in the CV group, but not in the HFO group (difference in slopes: p = 0.02). Across the population, deterioration in lung function was associated with male sex, white ethnicity, lower gestational age at birth, postnatal corticosteroids, oxygen dependency at 36 weeks postmenstrual age, and lower birth weight, but not ventilation mode. Conclusions: There was little evidence that the mode of ventilation affected changes in lung function over time.